2021
DOI: 10.3390/diseases9040086
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Dysplasia and Cancer Surveillance in Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a risk factor for the development of inflammation-associated dysplasia or colitis-associated neoplasia (CAN). This transformation results from chronic inflammation, which induces changes in epithelial proliferation, survival, and migration via the induction of chemokines and cytokines. There are notable differences in genetic mutation profiles between CAN in UC patients and sporadic colorectal cancer in the general population. Colonoscopy is the cornerstone for surveillance and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…This feedback loop of inflammation, DNA damage, and cell growth ultimately leads to remodeling the extracellular matrix and metastases (Dulai et al, 2016;(Rennoll, 2015;Saraggi et al, 2017). Last but not least, disbiosis of genotoxic microorganisms has been shown to have implications as a risk factor for carcinogenesis through decreased production of anti-inflammatory cytokines, such as IL-10 ( Reznicek et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feedback loop of inflammation, DNA damage, and cell growth ultimately leads to remodeling the extracellular matrix and metastases (Dulai et al, 2016;(Rennoll, 2015;Saraggi et al, 2017). Last but not least, disbiosis of genotoxic microorganisms has been shown to have implications as a risk factor for carcinogenesis through decreased production of anti-inflammatory cytokines, such as IL-10 ( Reznicek et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…According to studies, about half of colorectal cancer cases can be prevented or managed through risk modification and screening (Fisher et al, 2021). However, the condition of ulcerative colitis and its subsequent development into colitis-associated neo-plasia (CAN) give a unique challenges related to the supervision and management of dysplasia (Reznicek et al, 2021). The type of unconventional dysplasia has been known, but its natural history has not been well defined.…”
Section: Introductionmentioning
confidence: 99%
“…All things considered, with current therapy and under the best of circumstances, UC patients must undergo life-long surveillance colonoscopy for colon cancer, which cannot detect all neoplastic lesions leading to a high mortality rate[ 29 , 294 , 295 ]. And although total colectomy has been touted as a cure for the approximately 30% of UC patients who fail medical therapy or develop colon cancer, studies have shown that patients who have undergone ileal pouch/anal anastomosis have higher disability scores than patients with active UC[ 296 ].…”
Section: Discussionmentioning
confidence: 99%
“…Пациенты с ПСХ имеют более высокий риск развития КРР. Так, у больных с 20-летним анамнезом ЯК с сопутствующим ПСХ в 33% случаев был диагностирован КРР [17].…”
Section: факторы риска развития крр на фоне якunclassified